Technology assisted learning courseware for biological science - Lim, Hwa Yan (2019)

(untitled)
This project provides interactive educational courseware for Form 4 students in learning the biology subject. This project aims to develop a fun and interesting educational courseware for secondary school students. The main purpose of developing this project is to solve the problem that the students nowadays faced boring and complex content in the study of biology. In general, this project organizes information into categories and then integrate text, graphics, images, sound, animation, video and other media materials in both time and space, to integrating them and giving them interactive features. So that, to produce a variety of colorful multimedia application software products. The user interface is design to be more interactive than traditional, helping students learn and understand the course content. Therefore, by using this courseware, students have higher academic performance. This project consists of 5 Modules, which are Introduction Module, Experiment Module, Simulation Lab Module, Quiz Module and Mini Game Module. Furthermore, ADDIE model has been chosen as the project methodology for developing the courseware.